OP0207 The outcomes of limited cutaneous systemic sclerosis patients: a eustar database study. (12th June 2018) - Frantz, C.; Huscher, D.; Hachulla, E.; Balbir-Gurman, A.; Riemekasten, G.; Siegert, E.; Airo, P.; Joven, B.; Vettori, S.; Cozzi, F.; Ullman, S.; Czirjak, L.; et al.
Abstract : Background: Several studies have consistently showed that the extent of skin involvement has a major impact on disease prognosis in the diffuse cutaneous subtype of systemic sclerosis. The large majority of the ongoing clinical trials aim at identifying efficient drug in this subset. By contrast, little is known about the limited cutaneous subset (LcSSc) and the translation of the data coming for DcSSc to LcSSc is uncertain. Objectives: Therefore, our aim was to investigate skin and lung involvement trajectories of LcSSc patients using the large EUSTAR registry. Methods: We analysed the longitudinal data extracted from the EUSTAR cohort collected before February 2017. Worsening of skin fibrosis was defined by an increase in modified Rodnan skin score (mRSS) >3.5 points from baseline to 2nd visit. Interstitial lung disease (ILD) was defined by any fibrosis on imaging (X-ray/computed tomography). Worsening of ILD was defined by a decrease of FVC >10% from baseline to 2nd visit. For predicting models, predictors with p<0.2 in the univariate analysis were included in the logistic regression analysis. Results: 8013 LcSSc were included with a mean follow-up of about 3.3±3.7 years. At baseline, mean ±SD mRSS was 6±5 and ILD was present in 28.4% of all patients. Worsening of skin fibrosis was observed in 6.4% (19/298), 7.8% (97/1248) and 9.8% (289/2957) of LcSSc patients at 6, 12 and 24 months follow-up respectively. In multivariate analysis, variables predicting skin fibrosis progression were elevated European Scleroderma Study Group activity index (EScSG-AI) (OR [95 IC]: 1.22 [1.05–1.4], p=0.007) for 12 months progression and EScSG-AI (1.24 [1.13–1.38], p<0.001) and mRSS (0.95 [0.93–0.98], p=0.001) for 24 months progression. Worsening of ILD was observed in 11.7% (23/196) and 19.9% (65/326) of LcSSc patients with ILD at baseline, at 12 and 24 months follow-up respectively. In multivariate analysis, variables predicting ILD progression at 24 months were EScSG-AI >3 (OR [95 IC]: 3.8 [1.51–9.56], p=0.005), FVC (1.03 [1.01–1.04], p<0.001) and LVEF (0.91 [0.85–0.97], p=0.005). Conclusions: It appears that only few LcSSc patients progress for skin fibrosis ; this limits the use of mRSS in this subset and the potential of anti-fibrotic drugs of skin disease. However, a substantial rate of ILD progression was identified as well as relevant predictors. These results support the inclusion of LcSSc patients in SSc-ILD trials evaluating anti-fibrotic drugs. Our predictive models will be helpful to define enriched population in future clinical trials. Acknowledgements: This work was supported by an unrestricted grant from INVENTIVA Disclosure of Interest: None declared